(untitled) (Global Journal of Science Frontier Research, 2016)
This paper presents a model of the cosmic medium, which allows to describe the physical nature and microscopic structure of dark energy and has the macroscopic properties of both positive and negative pressure density. It is indicated that the cosmological constant Λ characterizes the elastic properties of the dark energy, and "antigravity universal law" is the law of elasticity Hooke. The evidence base is based on the results of experiments conducted in superfluid ³He-B in the pstate analogue projecting dark energy. In addition, for the construction of the resonance curves of the photoelectric effect in the near-Earth space environment, we used the results of observations obtained by space detector PAMELA, Fermi and detector AMS, installed on board the ISS.